2010
DOI: 10.1007/s10096-010-1098-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of diagnosing influenza within 24 hours of symptom onset in children 1–3 years of age

Abstract: Diagnosing influenza at an early stage of illness is important for the initiation of effective antiviral treatment. However, especially in young children, influenza often commences with an abrupt onset of fever, with full-blown respiratory symptoms developing only later. We determined the feasibility of diagnosing influenza in young children already during the first signs of the illness. During confirmed influenza activity, we obtained nasal swabs from children aged 1-3 years who presented as outpatients withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Several rapid test kits that can provide results within 15 min are available. The performance of these tests varies [26,27], but is usually good in children and during the early course of the illness when, also, the benefits of the antiviral treatment of influenza are greatest [10,25,28,29]. Pre-test probability of influenza Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several rapid test kits that can provide results within 15 min are available. The performance of these tests varies [26,27], but is usually good in children and during the early course of the illness when, also, the benefits of the antiviral treatment of influenza are greatest [10,25,28,29]. Pre-test probability of influenza Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that our viral culture method included also subsequent immunoperoxidase staining with monoclonal antibodies [22]. In previous studies, this method has yielded a sensitivity of approximately 90% when compared with polymerase chain reaction (PCR)-based assays for the detection of influenza [10,25]. Furthermore, because the controls were selected in a blinded manner from a very large database of influenza virus-negative children, the probability for any individual child who may have been false-negative for influenza to end up in the control group was low.…”
Section: Discussionmentioning
confidence: 99%
“…(7)(8)(9) In one study, the Actim Influenza A&B kit (Medix Biochemica, Joensuu, Finland) has been shown to be 90.0% sensitive for the detection of influenza A virus. (10) Some small studies have shown that a positive RAT spurs changes in clinical practice. (11)(12)(13) In this study, we investigated the effect of RAT for influenza on the proportion of antibiotic administration, additional diagnostic tests, and the length of stay (LOS) in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the sensitivity of DFA is higher than that of the rapid antigen test. Studies have shown that DFA sensitivity is higher among pediatric patients, especially displaying signs of high fever and spreading high amounts of viruses and decreasing with patients above 30 years of age (Heinonen et al 2011).…”
Section: Direct Fluorescence Antibody Assay (Dfa)mentioning
confidence: 99%